Ag+ implantation induces mechanical properties, cell adhesion and antibacterial effects of TiN/Ag multilayers in vitro. (September 2017) - Sun, Xiuhua; Gong, Huanhuan; Li, Dejun; Dong, Lei; Zhao, Mengli; Wan, Rongxin; Gu, Hanqing
Aim: This study aims to investigate the effect of Ag + implantation dose on the structure, hardness, adhesion strength, friction resistance, cell adhesion and antibacterial effects of TiN/Ag multilayers.Methods: Nanoscale TiN/Ag multilayers were deposited on Ti–6Al–4V substrates using multiarc ion plating. The multilayers were then implanted by Ag ions.Results: A distinct multilayer structure and large titanium nitride grains with better (111) crystallinity were proved. The hardness and elastic modulus of the multilayer reached 32.2 and 318.9 GPa, respectively. The largest critical load was 32.5 mN, and the minimum friction coefficient was 0.092. The mechanical properties, the cell proliferation and antibacterial properties of the multilayers with Ag + implantation were better than those without Ag + implantation.Conclusion: Our results indicate that a dose of 1 × 1017 ions/cm 2 induced an improvement in crystallinity, mechanical properties, as well as preferable cell adhesion and antibacterial effects.